Isolation, characterization, and effect of fluorescent pseudomonads on micropropagated sugarcane - Mehnaz, S.; Weselowski, B.; Aftab, F.; Zahid, S.; Lazarovits, G.; Iqbal, J.
In this study, we report on the isolation, identification, and characterization of seven fluorescent pseudomonads isolated from the roots, shoots, and rhizosphere soil of sugarcane and their impacts on the growth of sugarcane plantlets. 16S rRNA gene sequence of five isolates showed close homology with Pseudomonas putida, one with Pseudomonas graminis, and one with Pseudomonas fluorescens. Physiological and biochemical characterizations were determined using API50CH and QTS24 identification kits. The isolates were also subjected to tests for various known growth promoting properties including production of indole acetic acid, the ability to fix nitrogen via the presence of the nifH gene, and ability to solubilize phosphate. Biological control potential was determined from agar diffusion assays of HCN production and production of antifungal compounds against local isolates of Colletotrichum falcatum (that induces red-rot disease of sugarcane). Direct plant growth promoting effects were tested on sugarcane plantlets in tissue culture under gnotobiotic conditions. All seven isolates provided significant increases in fresh and dry masses but only five strains increased shoot height.